The Dynamics of Presidential Impeachment in the Indonesian Constitutional System: A Critical Study of the Constitutional Mechanism - Gede Githa Gede Githa; Faizal Alwi (Indonesian Civil Law Review, 2025)
The impeachment of the President is an important mechanism in maintaining accountability of power in the Indonesian constitutional system. Although it has been regulated in Articles 7A and 7B of the 1945 Constitution and strengthened through the Constitutional Court Law and the MD3 Law, this mechanism still leaves various problems, such as multiple interpretations of norms, the potential for politicization, and weak public participation. This study aims to examine the juridical and philosophical basis of impeachment and formulate recommendations for its improvement. The method used is normative legal research with a legislative and conceptual approach, as well as secondary data analysis The results of the study show that impeachment is a reflection of the principles of the state of law, democracy, and constitutionalism. However, its implementation needs to be strengthened through clarity of legal norms, strengthening the role of the Constitutional Court, transparency of the process, and public involvement. In conclusion, impeachment must be kept away from political interests and carried out objectively and accountably. This study recommends reformulation of technical regulations and increased constitutional awareness to ensure impeachment functions as a legal instrument rather than a political tool